Biallelic mutations in EXOC3L2 cause a novel syndrome that affects the brain, kidney and blood - Shalata, Adel; Lauhasurayotin, Supanun; Leibovitz, Zvi; Li, Hongbing; Hebert, Diane; Dhanraj, Santhosh; Hadid, Yarin; Mahroum, Mohammed; Bajar, Jacob; Egenburg, Sandro; Arad, Ayala; Shohat, Mordechai; et al. (Journal of medical genetics, 2019)
BackgroundDandy-Walker malformation features agenesis/hypoplasia of the cerebellar vermis, cystic dilatation of the fourth ventricle and enlargement of posterior fossa. Although Dandy-Walker malformation is relatively common and several genes were linked to the syndrome, the genetic cause in the majority of cases is unknown.ObjectiveTo identify the mutated gene responsible for Dandy-Walker malformation, kidney disease and bone marrow failure in four patients from two unrelated families.MethodsMedical assessment, sonographic, MRI and pathological studies were used to define phenotype. Chromosomal microarray analysis and whole-exome sequence were performed to unravel the genotype.ResultsWe report four subjects from two unrelated families with homozygous mutations in the Exocyst Complex Component 3-Like-2 gene (EXOC3L2).EXOC3L2 functions in trafficking of post-Golgi vesicles to the plasma membrane. In the first family a missense mutation in a highly conserved amino acid, p.Leu41Gln, was found in three fetuses; all had severe forms of Dandy-Walker malformation that was detectable by prenatal ultrasonography and confirmed by autopsy. In the second family, the affected child carried a nonsense mutation, p.Arg72*, and no detected protein. He had peritrigonal and cerebellar white matter abnormalities with enlargement of the ventricular trigones, developmental delay, pituitary hypoplasia, severe renal dysplasia and bone marrow failure.ConclusionWe propose that biallelic EXOC3L2 mutations lead to a novel syndrome that affects hindbrain development, kidney and possibly the bone marrow.